2023
DOI: 10.1111/ejh.14008
|View full text |Cite
|
Sign up to set email alerts
|

Failure of mobilization of hematopoietic stem cells associated with elevated serum levels of anti‐CD38 monoclonal antibody

Abstract: Daratumumab is an anti-CD38 antibody that is increasingly incorporated in induction regimens for treating patients with newly diagnosed multiple myeloma (NDMM).Previous reports have demonstrated a lower yield of hematopoietic stem cells (HSCs) after induction with daratumumab; however, none of them reported a failure to collect an adequate number of HSCs. We describe a case of adequate HSC mobilization failure in a patient who inadvertently received excessive doses of daratumumab and was confirmed by higher-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…A report indicated that elevated serum levels of anti-CD38 monoclonal antibody may affect mobilization by binding to low levels of CD38 antigen expression of CD34 + cells. 2 Predicting mobilization failure before it starts may enable patients to develop tailored strategies, such as omitting CTX in induction, monitor closely and use early plerixafor in case of low PB CD34 + cells count. It has been suggested that the negative effect of lenalidomide on mobilization can be overcome by chemo-mobilization.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A report indicated that elevated serum levels of anti-CD38 monoclonal antibody may affect mobilization by binding to low levels of CD38 antigen expression of CD34 + cells. 2 Predicting mobilization failure before it starts may enable patients to develop tailored strategies, such as omitting CTX in induction, monitor closely and use early plerixafor in case of low PB CD34 + cells count. It has been suggested that the negative effect of lenalidomide on mobilization can be overcome by chemo-mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…As novel drugs, such as daratumumab, pomalidomide, and carfilzomib, are increasingly incorporated into the first‐line induction therapies for MM, 2,3 traditional risk factors for PM are different. CASSEIOPIA, GRIFFIN, and several other phase 3 studies have supported that the daratumumab‐based triplet or quadruplet regimen as the first‐line therapy in induction 12,13,36,37 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations